Principles Of Cadmium Production And Their Application At The Outokumpu Zinc Plant In Kokkola - S. Fugleberg (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1973)
As a result of research work done during the planning of the Kokkola zinc plant it was found that a very efficient cementation of impurities from the suspension obtained after leaching copper and cadmium cakes was achieved by adding zinc dust to the batch without filtration after the leaching. All elements nobler than cadmium are precipitated with the exception of lead, which must be removed in a separate step. Using pure zinc dust, free from noble metals, the cadmium sponge produced will only contain elements that can be re- moved from cadmium by meltrefining. The process is thus : 1. Leaching and purification 2. Removal of lead (with BaCO3) 3. Precipitation of cadmium sponge with pure zinc dust 4. Meltrefining of briquetted sponge with NaOH for removal of Zn (and others) The paper deals with the removal of the most critical elements, i.e. Co, Ni, As, Sb, Cu, Pb, T1 in the liquid phase and Zn and T1 in the melt. A survey is also given of the behaviour of most of the other elements normally found in Cd raw material, such as Ge, Te, Se, Sn, In, Ga. It is shown that in most cases the benefit of an electrolysis in Cd production is very limited. In Kokkola 99.998% Cd is achieved by this method, but in favourable cases it may be possible to come quite close to five nines.